Experimental considerations support the use of artificial sentinel prey—a comment on Rodriguez‐Campbell et al - Marco Ferrante; Andy G. Howe; Gabor L. Lövei (Journal of Biogeography, 2024)

The potential of selected shade tree species for managing mirids and black pod disease infection in cocoa agroforestry systems in Ghana - Bismark Kwesi Asitoakor; Anders Ræbild; Richard Asare; Philippe Vaast; Andy G. Howe; Vincent Yao Eziah; Kwadwo Owusu; Eric Opoku Mensah; Daniel Ashie Kotey; Hans Peter Ravn (Crop Protection, 2024)

Multifunctional bioretention basins as urban stepping stone habitats for wildflowers and pollinators - Mona Chor Bjørn; Andy G. Howe (Urban Forestry & Urban Greening, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Diet of the European bison (Bison bonasus) in a forest habitat estimated by DNA barcoding - Ida Hartvig; Andy G. Howe; Emilie N. B. Schmidt; Cino Pertoldi; Jeppe Lund Nielsen; Rita M. Buttenschøn (Mammal Research, 2021)

Exploring structural habitat heterogeneity in sustainable urban drainage systems (SUDS) for urban biodiversity support - Rikke Juul Monberg; Andy G. Howe; Hans Peter Ravn; Marina Bergen Jensen (Urban Ecosystems, 2018)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Potential for exploitative competition, not intraguild predation, between invasive harlequin ladybirds and flowerbugs in urban parks - Andy G. Howe; Hans Peter Ravn; Christian Bressen Pipper; Alexandre Aebi (Biological Invasions, 2016)